Heart rate variability (HRV) signal analysis : clinical applications - Kamath, Markad V.; Watanabe, Mari A.; Upton, Adrian R. M. (Boca Raton : Taylor & Francis, 2013)
"Written for graduate students and professionals dealing with heart rate variability (HRV), this cutting-edge reference reviews how minute variations in the beat-to-beat heart rate are regulated. It explores how these variations can be used as a window to understanding the central and peripheral mechanisms that modulate the autonomic nervous systems. Explaining how HRV is characterized through simple statistics and frequency analysis in both healthy human subjects and patients with a variety of diseases, the book provides examples for methods that require mathematical techniques. The authors cite a variety of real-life medical situations and offer extensive end-of-chapter references"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Heart rate monitoring; Heart beat -- Measurement; Heart beat -- Physiological aspects; Heart function tests; Signal processing; Electronic books